1974
DOI: 10.1055/s-0028-1108042
|View full text |Cite
|
Sign up to set email alerts
|

Nierenpapillennekrosen

Abstract: Die Nierenpapillennekrose, herdförmige oder totale Nekrose der Papille und angrenzender Bezirke des Nierenmarkes, ist meistens eine Komplikation anderer renaler Grundkrankheiten. Häufigkeit, Ursache und klinischer Verlauf haben sich in den letzten drei Jahrzehnten deutlich verändert. Bei 15 749 Obduktionen fand sich in den Jahren 1961-1971 eine Häufigkeit von 1,51°/o (n = 238). Das Verhältnis von Männern zu Frauen betrug 1,1 : 1. 218 Patienten (91,50/o) waren über 50 Jahre, 188 (78,9°/o) über 60 Jahre alt. Der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…reported that the application of flurbiprofen axetil can cause renal papillary necrosis and renal tubulointerstitial inflammation [9,10]. As we all know, NSAIDs can inhibit COX enzymes and reduce renal blood flow by blocking prostaglandin-mediated dilation of the glomerular arterioles.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the application of flurbiprofen axetil can cause renal papillary necrosis and renal tubulointerstitial inflammation [9,10]. As we all know, NSAIDs can inhibit COX enzymes and reduce renal blood flow by blocking prostaglandin-mediated dilation of the glomerular arterioles.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Flurbiprofen axetil is a nonselective cyclooxygenase (COX) inhibitor, which can gather at the surgical incision and inhibit the inflammatory response, thereby reducing postoperative pain, so it is widely used in the perioperative period [8]. However, studies have shown that the use of flurbiprofen may cause renal papillary necrosis and tubulointerstitial inflammation [9,10]. Studies have shown that nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit the expansion of preglomerular arterioles mediated by prostaglandins by inhibiting COX enzymes, resulting in a decrease in renal blood flow.…”
Section: Introductionmentioning
confidence: 99%